An In-depth Analysis for Optimal Cable Tray Support Span - Wuk Jung, Sung; Oterkus, Erkan (Sustainable Marine Structures, 2020)
Nowadays, it is crucial to reduce the cost of the overall project so that the competitiveness of offshore oil and gas without compromising on quality or safety can be achieved. This study investigates how to define the longest cable tray support span considering constructability in order to reduce the number of supports which is a chief cost of a cable tray system. This study presents not only material and geometry frequently used for cable tray but also the formula to estimate the maximum cable load which can be installed within cable tray. To verify the longest span without increasing the crosssection of cable tray, finite element modelling approach was employed based on ANSYS and comparisons were made between numerical analysis and simplified hand calculation. The constructability for the longer span obtained from finite element analysis has been validated in view of manual handling of the cable tray. It is shown that the optimal span suggested in this paper can lead to a better economic benefit without degrading the constructability. For instance, as the span is longer, the cost of material as well as construction manpower can be saved. It is also expected that this approach will contribute to enhance the competitiveness of offshore oil and gas. ER